Wpływ zasad religijnych na ukształtowanie systemu rachunkowości - Czerny, Małgorzata (Annales. Etyka w Życiu Gospodarczym, 2016)
Undoubtedly, such factors as different cultural background affects ‘the shape’ ofeconomy. The impact of cultural factors on the economy, as well as its specificfields (particularly accounting), has been studied by, among others, Mueller, Hofstedeand Gray. Reflections on the topic were also conducted in Polish literature,although relatively late. One of the cultural factors is, beyond doubt, religion, formingsome ethical attitudes through the transfer of certain values, which becomea guide to individual actions, and exerting an obvious influence on the applicablestandards in a society. The author does not pretend to consider the relations betweenreligion and ethics, in the article only issues concerning possible to demonstrateinfluence of religious norms on accounting are raised. The aim is briefly to discussthe impact of Christianity, Islam and Confucianism on accounting systems and practices,based on literature studies. In conclusion, the question arises about the senseof the convergence of accounting standards, at least in the context of the currentefforts undertaken in this field.